Phylogenetic Investigation of Population Changes when using Bacteriophage to Control Salmonella Typhimurium and Escherichia coli infections in Pigs - Atterbury, Robert J (2024)
Diarrhoeal disease is the third largest cause of mortality in children under 5 years old, leading to approximately half a million deaths per annum globally. Bacterial infections are thought to be responsible for just under half of these deaths, with Enterotoxigenic Escherichia coli (ETEC) and Nontyphoidal Salmonella (NTS) among the most frequently cited causes. Coinfection with these pathogens has been detected in up to half of infant diarrhoea cases, and this may be associated with more severe disease. ETEC and Salmonella Typhimurium also cause severe diarrhoea in piglets, leading to morbidity, mortality, significant economic loss and the risk of disease transmission in the human food chain. Hence, pigs have been used as a model of bacterial diarrhoea, both for veterinary research and as a proxy for human infant infection. Antimicrobial resistance (AMR) in both ETEC and Salmonella is a significant and growing global challenge in both humans and animals and alternative treatments are urgently needed. Bacteriophage (viruses which specifically infect bacteria) have been mooted as one such alternative.